2002
DOI: 10.1111/j.1750-3639.2002.tb00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐induced Apoptotic Neurodegeneration in the Developing Brain

Abstract: Physiological cell death (PCD), a process by which redundant or unsuccessful neurons are deleted by apoptosis (cell suicide) from the developing central nervous system, has been recognized as a natural phenomenon for many years. Whether environmental factors can interact with PCD mechanisms to increase the number of neurons undergoing PCD, thereby converting this natural phenomenon into a pathological process, is an interesting question for which new answers are just now becoming available. In a series of rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
174
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(182 citation statements)
references
References 57 publications
6
174
1
1
Order By: Relevance
“…54 All lead to apoptosis in a variety of cells. [55][56][57][58] Death induced in C8 and A9 cells after exposure to EtOH (2.5%), CHX (25 mg/ml), or CPT (20 mM) for 18 h was determined by trypan blue (TB) exclusion assay. Owing to their sensitivity to low serum (1% FBS), untreated control C8 cells manifested of the order of 15% cell death ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…54 All lead to apoptosis in a variety of cells. [55][56][57][58] Death induced in C8 and A9 cells after exposure to EtOH (2.5%), CHX (25 mg/ml), or CPT (20 mM) for 18 h was determined by trypan blue (TB) exclusion assay. Owing to their sensitivity to low serum (1% FBS), untreated control C8 cells manifested of the order of 15% cell death ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Activation of NMDARs is essential for long-term potentiation and spatial learning and memory (Malenka and Bear, 2004), and NMDAR blockade results in impaired synaptic plasticity manifested as adverse effects on learning and memory (Sakimura et al, 1995;Shimizu et al, 2000). It has been shown that higher doses of ketamine can induce neuroapoptosis in rodents (Maxwell et al, 2006;Olney et al, 2002a;Wang et al, 2005) and primates (Haberny et al, 2002;Slikker et al, 2007b;Wang et al, 2006) during early development. In agreement, we have previously reported that ketamine induces motor neuron toxicity in zebrafish embryos .…”
Section: Discussionmentioning
confidence: 99%
“…Reports also show that exposure of the developing brain to a clinically relevant cocktail of anesthetics that has both NMDA antagonist and GABA mimetic properties results in an extensive pattern of neuroapoptosis, and subsequent cognitive deficits (Olney et al, 2002b). Several reports have illustrated that ketamine can induce neuronal apoptosis when administered in high doses and/or for prolonged durations during susceptible periods of development in rodents (Maxwell et al, 2006;Olney et al, 2002a;Wang et al, 2005) and primates (Haberny et al, 2002;Slikker et al, 2007a;Wang et al, 2006) and these effects can manifest on later disruptions in cognitive function (Paule et al, 2011). To minimize risks to children exposed to anesthesia, it is paramount to understand how anesthetic drugs affect the developing nervous system and whether those effects can be ameliorated or prevented.…”
Section: Introductionmentioning
confidence: 99%
“…Blockade of the NMDAR induces widespread apoptosis and worsening of ongoing neurodegeneration in the developing and adult central nervous system. [44][45][46] Environmental enrichment, which stimulates synaptic activity, inhibits spontaneous apoptosis in the hippocampus and is neuroprotective. 47 Regarding the consequences of the decrease in function of extrasynaptic NMDARs, coupled to cell-death pathways, 14 a protective role might be suggested.…”
Section: Figurementioning
confidence: 99%